Principles‐Based versus Rules‐Based Auditing Standards: The Effect of the Transition from AS2 to AS5. (14th June 2015) - Sin, Fang Yun; Moroney, Robyn; Strydom, Maria
<x xml:space="preserve">Abstract</x> The transition from a rules‐based auditing standard (AS2) to a principles‐based auditing standard (AS5) provides a context to assess how such a change impacts audit outcomes. Under a rules‐based auditing standard, audit processes are relatively uniform, unscaleable and include significant redundancy. Under a principles‐based auditing standard, audit effort can be directed to where risk is greatest; audits are scalable and can be customized. We find that the post‐SOX shedding of risky clients by the Big 4 meant that non‐Big 4 clients were more likely than Big 4 clients to disclose material internal control weaknesses (MICWs) when assured under AS2. This gap narrowed significantly following the transition to AS5, when risk‐based customized audits were possible which benefited Big 4 firms to a greater extent than non‐Big 4 firms.